Apolipoprotein E mediates evasion from hepatitis C virus neutralizing antibodies - Fauvelle, Catherine; Felmlee, Daniel J.; Crouchet, Emilie; Lee, Ji Young; Heydmann, Laura; Lefèvre, Mathieu; Magri, Andrea; Hiet, Marie-Sophie; Fofana, Isabel; Habersetzer, François; Foung, Steven K. H.; Milne, Ross; et al. (Gastroenterology, 2016)
Background & Aims - Efforts to develop an effective vaccine against hepatitis C virus (HCV) have been hindered by the propensity of the virus to evade host immune responses. HCV particles in serum and in cell culture associate with lipoproteins, which contribute to viral entry. Lipoprotein association has also been proposed to mediate viral evasion of the humoral immune response, though the mechanisms are poorly defined. - Methods - We used small interfering RNAs to reduce levels of apolipoprotein E (apoE) in cell culture−derived HCV−producing Huh7.5-derived hepatoma cells and confirmed its depletion by immunoblot analyses of purified viral particles. Before infection of naïve hepatoma cells, we exposed cell culture−derived HCV strains of different genotypes, subtypes, and variants to serum and polyclonal and monoclonal antibodies isolated from patients with chronic HCV infection. We analyzed the interaction of apoE with viral envelope glycoprotein E2 and HCV virions by immunoprecipitation. - Results - Through loss-of-function studies on patient-derived HCV variants of several genotypes and subtypes, we found that the HCV particle apoE allows the virus to avoid neutralization by patient-derived antibodies. Functional studies with human monoclonal antiviral antibodies showed that conformational epitopes of envelope glycoprotein E2 domains B and C were exposed after depletion of apoE. The level and conformation of virion-associated apoE affected the ability of the virus to escape neutralization by antibodies. - Conclusions - In cell-infection studies, we found that HCV-associated apoE helps the virus avoid neutralization by antibodies against HCV isolated from chronically infected patients. This method of immune evasion poses a challenge for the development of HCV vaccines.